Summary Proceedings: of the Forty-Fourth Annual Meeting of the Board of Governors September 26-28, 1989 - International Monetary Fund; The World Bank (Washington : International Monetary Fund, 1989)
These Summary Proceedings include statements, or portions of statements, or portions of statements, relating to the work of the Fourth Annual Meeting of the Board of Governors of the International Monetary Fund was held in Washington, D.C from September 26 through September 28, 1989, jointly with the Annual Meetings of the Boards of Governors of the World Bank Group.
usc 26/08/2021
Ref.